Magnet-Retained Facial Prosthesis Combined with Maxillary Obturator. (8th May 2013) - Hatami, Mahnaz; Badrian, Hamid; Samanipoor, Siamak; Goiato, Marcelo Coelho
Abstract : Prosthetic rehabilitation of the midfacial defects has always perplexed prosthodontists. These defects lead to functional and esthetic deficiencies. The purpose of this clinical case report was the presentation of the prosthetic rehabilitation of an extraoral-intraoral defect using two-piece prosthesis magnetically connected. This prosthesis has dramatically improved the patient's speech, mastication, swallowing, and esthetic.